A history of Jewish-Muslim relations : from the origins to the present day - Meddeb, Abdelwahab; Stora, Benjamin, 1950-; Todd, Jane Marie, 1957-; Smith, Michael B. (Michael Bradley), 1940- (Princeton University Press, 2013)
"This is the first encyclopedic guide to the history of relations between Jews and Muslims around the world from the birth of Islam to today. Richly illustrated and beautifully produced, the book features more than 150 authoritative and accessible articles by an international team of leading experts in history, politics, literature, anthropology, and philosophy. Organized thematically and chronologically, this indispensable reference provides critical facts and balanced context for greater historical understanding and a more informed dialogue between Jews and Muslims"--Jacket.